2-[(Pyrimidin-2-ylamino)methyl]pheno1 - Xu, J.; Gao, S.; Ng, S.W. (International Union of Crystallography, 2011)
In the title compound, C(11)H(11)N(3)O, the aromatic rings at either ends of the -CH(2)-NH-link are twisted by 72.58 (8)degrees; the hydroxy substituent is a hydrogen-bond donor to an N atom of the pyrimidine ring. The other N atom of the pyrimidine ring is a hydrogen-bond acceptor to the amino group of an inversion-related molecule.